Research on slope stability of open-pit mine under coupled seepage-stress - LI Zhu; XIE Feng (Gong-kuang zidonghua, 2018)
In order to research influence of coupled seepage field and stress field on slope stability of open-pit mine, ABAQUS finite element analysis software was used to establish seepage-stress coupled control equation and finite element model of open-pit mine, and slope stability of open-pit mine was researched under coupled seepage-stress. The research results show that rock strength decreases gradually with soaking time prolonging, but when the rock reaches saturation, rock strength tends to be stable. Slope displacement under coupled seepage-stress is larger than the one without seepage, and safety factor of slope reduces with decrease of permeability coefficient of slope body. In open-pit mine field, deep displacement of monitoring points reduces after a support scheme based on shotcrete and prestressed anchor cable is implemented, which shows that the scheme can effectively control slope displacement and reduce adverse effect on slope stability of coupled seepage-stress.